Fungsi Prospektus Penawaran Waralaba dalam Perjanjian Waralaba di Indonesia - Fisiliya Aricka Yuliyarsih (Fakultas Hukum Universitas Islam Jember, 2013)
Protection against the procedure of confidential information and know-how (in the Franchise Disclosure Document) from the franchisor to the franchisee is under franchised agreement. Some important things that need to be done in the framework of juridical to regulate the franchise lawarefranchise registration, disclosure principle, franchise association, franchise code of ethics and guidelines of the franchise contract. Government Regulation No. 42/2007 stipulates that a franchise offering prospectus is the obligation of franchisor to the franchisee and the franchisor requires registering the franchise offering prospectus before making a franchise agreement with a franchisee. The registration of franchise offering prospectus is made to get the Certificate of Registration of Franchising (STPW). Provisions of fines and administrative sanctions apply to franchisees who do not register their prospectus.